Biomarkers for early complications post hematopoietic cell transplantation: Insights and challenges - Balakrishnan, Balaji; Kulkarni, Uday Prakash; Pai, Aswin Anand; Illangeswaran, Raveen Stephen Stallon; Mohanan, Ezhilpavai; Mathews, Vikram; George, Biju; Balasubramanian, Poonkuzhali (Frontiers in Immunology, 2023)
Hematopoietic cell transplantation is an established curative treatment option for various hematological malignant, and non-malignant diseases. However, the success of HCT is still limited by life-threatening early complications post-HCT, such as Graft Versus Host Disease (GVHD), Sinusoidal Obstruction Syndrome (SOS), and transplant-associated microangiopathy, to name a few. A decade of research in the discovery and validation of novel blood-based biomarkers aims to manage these early complications by using them for diagnosis or prognosis. Advances in this field have also led to predictive biomarkers to identify patients’ likelihood of response to therapy. Although biomarkers have been extensively evaluated for different complications, these are yet to be used in routine clinical practice. This review provides a detailed summary of various biomarkers for individual early complications post-HCT, their discovery, validation, ongoing clinical trials, and their limitations. Furthermore, this review also provides insights into the biology of biomarkers and the challenge of obtaining a universal cut-off value for biomarkers.